Experimental Study of Sea Wave Power Plant with Mechanical Buoying System - Juhana; Abdul Rozak, Ojak; Citra Dewa, Digo (UIR PRESS, 2022)
The need for electrical energy in Indonesia continues to increase, triggering an electrical energy crisis due to the increasing number of consumers of electrical energy which has an impact on the reduction of non-renewable fossil energy sources. Alternative energy sourced from new and renewable energy is needed, the use of electric generators from ocean wave energy in coastal areas needs to be empowered to be used as electrical energy that is useful for the community. This ocean wave power plant consists of: generator, power storage and voltage riser. A fixed magnetic generator connected to the buoy ball, the kinetic energy and potential energy of the ocean waves move the buoy ball so that the generator can rotate and produce electrical energy. This system can be used as a 12 V direct current (DC) battery charger as a backup energy supply and then increased to 220 V alternating current (AC) using an inverter. The average result of generator rotation is 182.34 ratio per minute (RPM). The average voltage generated by the generator is 12.53 V and the average current is 1.06 A and the output voltage of the inverter is 217 V when the load is 100 W.